4-Formylazetidin-2-ones, synthon for the synthesis of (2R,3S) and (2S,3R)-3-amino-2-hydroxydecanoic acid (AHDA) - Shirode, N. M.; Deshmukh, A. R. A. S. (Tetrahedron, 2006)
An efficient synthesis of 3-amino-2-hydroxydecanoic acid (AHDA), a nonproteinogenic amino acid, using enantiopure 3-benzyloxy-4-formylazetidin-2-one as a building block is described. Both the enantiomers of AHDA have been synthesized from the corresponding enantiomer of 3-benzyloxy-4-formylazetidin-2-one in good yield and optical purity. (c) 2006 Published by Elsevier Ltd.
Keywords: Amino acids; azetidin-2-ones; Staudinger reaction; stereoselective synthesis; Wittig reaction

Double intramolecular oxymercuration: stereoselective synthesis of highly substituted bis-tetrahydrofuran - Mohapatra, Debendra K.; Mohapatra, Seetaram; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
Stereoselective intramolecular oxymercuration has been demonstrated as the key reaction for the efficient preparation of mono- and dihydroxylated unsymmetrical bis-tetrahydrofuran skeletons present in naturally occurring biologically active acetogenins using carbohydrates. These trans- and syn-selective intramolecular oxymercurations were explored in an enantio selective synthesis of the bis-tetrahydrofuran skeleton of mucoxin. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: acetogenins; Barton-McCombie deoxygenation; demercuration; intramolecular oxymercuration; unsymmetrical bis-tetrabydrofuran; Wittig reaction

Synthesis of the C19-C34 segment of amphidinolide C - Mohapatra, Debendra K.; Rahaman, Hasibur; Chorghade, Mukund S.; Gurjar, Mukund K. (Synlett, 2007)
The synthesis of the C19-C34 segment of amphidinolide C is described. The key steps include the Mioskowski's Lewis acid catalyzed epoxide opening with the alcohol, ring-closing metathesis, Wittig reaction, and Nozaki-Hiyama-Kishi coupling reaction.
Keywords: amphidinolide C; Cytotoxic; Nozaki-Hiyama-Kishi coupling; Ring-closing metathesis; Wittig reaction

Synthesis of the C14-C29 segment of amphidinolide U utilizing a tandem dihydroxylation-S(N)2 cyclization protocol - Mohapatra, Debendra K.; Rahaman, Hasibur (Synlett, 2008)
The synthesis of the C14-C29 subunit of amphidinolide U is described. The key steps include the trans-2,5-disubstituted tetrahydrofurans via a highly diastereoselective and high yielding tandem dihydroxylation-S(N)2 cyclization, Wittig reaction, and Nozaki-Hiyama-Kishi coupling reaction.
Keywords: amphidinolide U; Cytotoxic; Nozaki-Hiyama-Kishi coupling; tandem dihydroxylation-S(N)2 cyclization; Wittig reaction

Total synthesis of (S)-(-)-curvularin: a ring-closing-metathesis-based construction of the macrocyclic framework - Mohapatra, Debendra K.; Rahaman, Hasibur; Pal, Rita; Gurjar, Mukund K. (Synlett, 2008)
A convergent, flexible, and efficient approach to the synthesis of curvularin is described. Key step is the high-yielding macrocyclic ring formation by ring-closing metathesis (RCM) using the Grubbs second-generation catalyst.
Keywords: curvularin; Cytotoxic; Pinnick oxidation; Ring-closing metathesis; Wittig reaction

Enantioselective total synthesis of (2S,3R,4R)-D-xylo-phytosphingosine from substituted azetidin-2-one - Pandey, Ganesh; Tiwari, Dharmendra Kumar (Tetrahedron Letters, 2009)
Enantiomerically pure (2S,3R,4R)-D-xylo phytosphingosine is synthesized in 36% overall yield in seven steps from known beta-lactam (8) derived from D-mannitol triacetonide. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: beta-lactam; Enantioselective synthesis; Sphingosine; Wittig reaction

Stereoselective synthesis of the densely functionalized C1-C9 fragment of amphidinolides C and F - Mohapatra, Debendra K.; Dasari, Pavankumar; Rahaman, Hasibur; Pal, Rita (Tetrahedron Letters, 2009)
The synthesis of the C1-C9 subunit of amphidinolides C and F is described. Key steps include tandem Sharpless asymmetric dihydroxylation-S(N)2 cyclization reaction, Lewis acid-mediated epoxide opening, Wittig reaction, and Wacker oxidation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amphidinolide C and F; Cytotoxic; Tandem dihydroxylation-S(N)2; Wacker oxidation; Wittig reaction

Concise synthesis of (2S,3S,4S)-2-(Hydroxymethyl)pyrrolidine-3,4-diol (LAB1) - Upadhyay, Puspesh K.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
The synthesis of (2S,3S,4S)-2-(hydroxymethyl)pyrrolidine-3,4-diol (LAB1) from Garner's aldehyde is described using the Sharpless asymmetric dihydroxylation as the key step.
Keywords: alkaloid; azasugars; diastereoselectivity; Garner's aldehyde; pyrrolidine; Wittig reaction

Short and efficient synthesis of (S)-(+)-2-(Hydroxymethyl)-6-piperidin-2-one - Upadhyay, Puspesh K.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A concise synthesis of (S)-(+)-2-(hydroxymethyl)-6-piperidin-2-one is described that employs L-aspartic acid as chiral pool starting material and Wittig reaction as the key step.
Keywords: Amino acid; Hydrogenation; L-aspartic acid; pipecolate; piperidone; Wittig reaction

Enantiospecific route to (+)-(1R, 3S)-cis-chrysanthemic acid from (-)-D-pantolactone(1) - Hajare, Atul K.; Datrange, Laxmikant S.; Murthy, Y. L. N.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2011)
In this paper, a novel route for the synthesis of (+)-(1R,3S)-cis-chrysanthemic acid is described. The use of readily available (-)-D-pantolactone as a starting point, application of ring-closing metathesis to form the cyclopentene intermediate, and Haller-Bauer/Grob-type fragmentation to form the target compound are the highlights of the present synthesis.
Keywords: alkenes; Metathesis; ring closure; stereoselective synthesis; Wittig reaction

Short synthesis of (2S,3S)-3-hydroxypipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Pawar, Kailash P. (Tetrahedron Letters, 2013)
A convenient synthesis of (2S,3S)-3-hydroxypipecolic acid starting from cheap and abundant L-(+)-tartaric acid has been achieved. The strategy employs selective ester reduction and reductive lactamization as key steps. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Reductive lactamization; Selective deprotection; Wittig reaction

Croncise organocatalytic route to protected (2S, 4R)-4-hydroxyornithine and(+)-pseudohygroline - Jha, Vishwajeet; Kumar, Pradeep (Synlett, 2014)
A practical, efficient, and organocatalytic approach to the synthesis of (2S,4R)-4-hydroxyornithine and (+)-pseudohygroline is reported using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and Horner-Wadsworth-Emmons olefination reaction of an aldehyde as the key step.
Keywords: aldehydes; Amination; Amino alcohols; cyclization; Enantioselectivity; Wittig reaction

Formal total synthesis of (-)-kumausallene - Das, Shyamsundar; Ramana, Chepuri V. (Tetrahedron, 2015)
Deacetylkumausyne-a penultimate intermediate in Tang's total synthesis of (-)-kumausallene has been synthesized employing a chiral pool approach and thus culminating in a formal total synthesis of kumausallene. The opening of an epoxide with alkyne (use of Birch reduction for the selective construction of E-pent-3-enyl group) and C-allylation have been used to introduce the pendant alkenyl side chains. Initial attempts to execute an alternative to Tang's route comprising a prior installation of the bromoallene unit via bromoetherification and subsequent S(N)2 displacement are unsuccessful. To overcome this, an alternative approach was developed to arrive at Deacetylkumausyne (another natural product that has been synthesized and characterized by Tang's group). Thus, this overall exercise has culminated in a formal total synthesis of (-)-kumausallene. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bis-THF natural products; Chiral pool; Deacetylkumausyne; Total synthesis; Wittig reaction

Synthesis and tyrosinase inhibition activity of trans-stilbene derivatives - Ismail, Tabasum; Shafi, Syed; Srinivas, Jada; Sarkar, Dhiman; Qurishi, Yasrib; Khazir, Jabeena; Alam, Mohammad Sarwar; Kumar, Halmuthur Mahabalarao Sampath (Bioorganic Chemistry, 2016)
Synthesis of a focussed library of trans-stilbene compounds through Wittig and other base catalysed condensation reactions is presented. The synthesized stilbenes were screened for their inhibitory potential against murine tyrosinase activity to explore the structure activity relationship (SAR). Presence of electron withdrawing group (-CN) at the double bond and hydroxyl group or halogen atom especially at para-position on the aromatic rings was found to significantly elevate the inhibitory activity. Among all the compounds screened, compounds 2, 6, 8, 10, 11, 15 and 21 were found to exhibit appreciable inhibitory activity. Compound 21 ((E)-2,3-bis(4-Hydroxyphenyl) acryonitrile) was found to be the most active with an IC50 value of 5.06 mu M which is less than half of the value 10.78 mu M observed for resveratrol (common standard used in murine tyrosinase activity studies) under similar conditions. The results obtained from the present study reveal structural/functional group sensitivity for the tyrosinase inhibitory activity of stilbenoid moieties and are expected to be very helpful for the design and synthesis of novel, selective and effective tyrosinase inhibitors. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Electron withdrawing groups; Murine tyrosinase activity; Resveratrol; Stilbenoids; Tyrosinase inhibitors; Wittig reaction

Wittig reactions of maleimide-derived stabilized ylides with alkyl pyruvates: concise approach to methyl ester of (+/-)-chaetogline A - Shelar, Santosh V.; Argade, Narshinha P. (Synthesis-Stuttgart, 2021)
A facile synthesis of methyl ester of chaetogline A is reported starting from the corresponding methyl 1-methyltryptophanate-derived- maleimide. A stereoselective Wittig olefination with a carbonyl function in methyl pyruvate followed by phosphorous pentoxide-induced- regioselective dehydrative cyclization are the essential reactions. An acid-induced thermodynamically driven stereoselective beta- to alpha-position migration of the exocyclic C=C bond unit in ethyl tetrahydroindolizinoindolylidenepropanoate is described.
Keywords: Amino acid; chaetogline A; dehydrative cyclization; maleimide; methyl pyruvate; Natural product; Wittig reaction

Total synthesis of 12, 13-dibenzyl-banistenoside B and analogs - Patil, Suhag S.; Jachak, Gorakhnath R.; Krishna, Gamidi Rama; Argade, Narshinha P.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2022)
Banistenosides A and B possessing a unique ``azepino(1,2-a)tetrahydro-beta-carboline'' carbon framework were isolated from the stem of Banisteriopsis caapi and showed MAO-A inhibition. Herein, we report the total synthesis of dibenzyl derivative of the untouched natural product in the last two decades, Banistenoside B. The key steps involve construction of 6.5.6.7 tetracyclic core using Pictet-Spengler reaction and intramolecular amide coupling. The stereoselective glycation was achieved through Hotha's protocol using gold catalyst, and silver triflate in the late stage of synthesis. The stereochemistry of most of the essential compounds were confirmed by X-ray crystallography.
Keywords: Au-catalyst; Multiple steps total synthesis; Natural products; Pictet-Spengler reaction; Wittig reaction